Validation of a questionnaire assessing artificial intelligence use in secondary mathematics education in Peru - Susanibar Ramirez, Edgar Tito; Tapia Díaz, Abel; Torres Gallegos, Rudy Ricardo; Andrade Girón, Elia Clorinda; Tocto-Cano, Esteban; López-Gonzales, Javier Linkolk (Frontiers in Education, 2026)
The aim of this study was to adapt and validate a questionnaire to measure the use of artificial intelligence (AI) applications in mathematics teaching by Peruvian secondary school teachers. A previously validated instrument from Jordan was translated, culturally adapted, and psychometrically validated in the Peruvian context. The study followed a quantitative, cross-sectional, and psychometric design with intentional non-probabilistic sampling. The sample included 150 teachers for exploratory analysis and 266 for confirmatory analysis. The validation process involved expert judgment, reliability analysis, exploratory factor analysis, and confirmatory factor analysis. The instrument showed excellent internal consistency (Cronbach's α = 0.96) and sampling adequacy (KMO = 0.95). EFA identified a three-factor structure explaining 66% of the variance, later reorganized into two dimensions: didactic use of AI and strategic and formative use of AI. CFA supported a second-order hierarchical model, showing strong factor loadings. Despite moderate fit indices, the questionnaire demonstrates conceptual validity and practical relevance. It is a reliable tool for assessing AI-related teaching practices and supporting teacher training and educational innovation in Peru and Latin America, with potential to inform inclusive and equitable approaches to artificial intelligence integration in secondary mathematics education.